2008
DOI: 10.1111/j.1600-0722.2008.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide alters decorin and biglycan synthesis in rat alveolar bone osteoblasts: consequences for bone repair during periodontal disease

Abstract: A prime pathogenic agent associated with periodontitis is lipopolysaccharide (LPS) derived from Porphyromonas gingivalis. This study investigated the effects of P. gingivalis LPS on osteoblasts, which are responsible for alveolar bone repair. Bone cells were obtained from explants of rat alveolar bone chips and cultured with 0–200 ng ml−1 of P. gingivalis LPS. Porphyromonas gingivalis LPS significantly increased cell proliferation and inhibited osteoblast differentiation, as judged by reduced alkaline phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…This result further supports proposed roles for biglycan synthesis in directing proliferation and initiation of osteoblast differentiation in bone derived MSCs/precursor cells (Waddington et al, 2003b;Roberts et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…This result further supports proposed roles for biglycan synthesis in directing proliferation and initiation of osteoblast differentiation in bone derived MSCs/precursor cells (Waddington et al, 2003b;Roberts et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…As previous studies (28,29), our results showed that CS was the predominant sulfated glycosaminoglycan present in the injured femurs. ESWT increases CS expression (14 th day).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 71%
“…Although host response cannot be estimated in our in vitro study, the suppression of ALP activity under concentration-dependent influence of E. faecalis through still unknown mechanisms is in agreement with the above statements. These cell differentiation-related outcomes are supported by several research projects studying different bacterial effects on osteoblast cell differentiation [37,38].…”
Section: Discussionmentioning
confidence: 98%